Strategies for Strengthening Local Businesses through Digital Marketplace Transformation in the New Economy Era in Bone Regency - Andi Amitya Resty Dwiyanti; Zulkifli Ayub; Masriadi Masriadi; Asdar Asdar; Abdul Sahid (Universitas Medan Area, 2025)
This study analyzes the digital transformation of marketplaces as a strategy to strengthen micro, small, and medium enterprises (MSMEs) in Bone Regency, South Sulawesi. The background of this study is based on the digital technology adoption gap between urban and rural areas, which impacts the competitiveness of MSMEs. This study employs a qualitative approach with a case study design, involving 15 informants comprising business operators, marketplace platform managers, MSME facilitators, and local government representatives. Data were collected through semi-structured interviews, observations, and document analysis, then analyzed using the Miles, Huberman, and Saldana model to identify key themes. The findings reveal five key themes: (1) the motivation to adopt marketplaces is driven by the need to expand market reach and adapt to changing consumer behavior; (2) key enablers include training and technical assistance, while barriers include low digital literacy, infrastructure limitations, and logistical challenges; (3) digitalization has a positive impact on sales growth and changes in consumer behavior, particularly among younger generations; (4) local-based mentoring strategies and entrepreneurial communities such as Tangan Di Atas (TDA) are effective in accelerating digital adaptation; and (5) government policies support training and business legality, but collaboration with local platforms is still limited. This study highlights the importance of multi-actor collaboration and contextualized policy interventions to build inclusive, resilient, and sustainable digital marketplace ecosystems in rural areas, providing actionable insights for regional governments and stakeholders in strengthening rural digital economies.